Cochin Creole and the perils of casteist cosmopolitanism: Reading Requiem for the Living - J Devika (The Journal of Commonwealth Literature ﻿, 2015)
This article takes issue with prominent ways of interpreting the cosmopolitanism often attributed to Kerala State, India. By virtue of its geographical location, from medieval times Kerala developed deep historical connections with European, Arabian, and South-East Asian societies. However in contemporary evocations of Kerala’s cosmopolitanism, the historical connections to South-East Asian societies are conspicuous by their absence. Caste Hindu legacies have been privileged implicitly in these and, as a result, hybrid communities can only be perceived as “miscegenated”. They are, therefore, excluded from the legacies of national culture. Johny Miranda’s recent novella Requiem for the Living (2013), tries to end this invisibility by articulating the present of one such community, the Parankis of Cochin. On the one hand, it both challenges and complicates existing identities such as the “Anglo-Indian” and the “Luso-Indian”, revealing their elite moorings and dualistic conception of hybridity. On the other hand, it departs from the long history of the implications of novel-writing in projects of caste-community identity construction in Malayali society. In doing so, it directs our attention towards the possibilities of unearthing “subaltern cosmopolitanism”, which may indeed be more appropriate for contemporary challenges in the specific postcolonial context that is contemporary Kerala.